Avaliação in vitro da atividade inibitória de Lactobacillus spp., isolados do inglúvio e cecos de aves sobre Salmonella - Barros, M. R. [UNESP]; Andreatti Filho, Raphael Lucio [UNESP]; Lima, E. T. [UNESP]; Crocci, J. A. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2009)
Inglúvios e cecos de reprodutoras comerciais de frangos de corte foram utilizados para o isolamento de Lactobacillus spp. As estirpes isoladas foram caracterizadas como Gram-positivo, catalase negativo, produtoras de gás em glicose, não produtoras de H2S em triple sugar iron e identificadas pela reação em cadeia da polimerase como Lactobacillus reuteri e Lactobacillus salivarius. A utilização da técnica spot-on-the-lawn para avaliação da inibição in vitro permitiu a análise de vários microrganismos simultaneamente. Todas as estirpes isoladas inibiram in vitro S. Enteritidis fagotipo 4, S. Enteritidis fagotipo 28, S. Typhimurium, S. Pullorum, S. Agona, S. Anatum, S. Dublin e S. Senftenberg.

Crops and ceca of commercial broiler breeders were used for the isolation of Lactobacillus spp. The isolated samples were characterized by Gram positive staining, negative catalase test, production of gas from glucose, negative for H2S production from triple sugar iron, and were identified by the polymerase chain reaction as Lactobacillus reuteri and Lactobacillus salivarius. The use of the spot-on-the-lawn technique, with modifications, for the evaluation of the in vitro inhibition made it possible the simultaneous analysis of several microrganisms. All the crop and ceca isolated microorganisms presented an in vitro inhibitory effect against strains of Salmonella Enteritidis fagotype 4, S. Enteritidis fagotype 28, S. Typhimurium, S. Pullorum, S. Agona, S. Anatum, S. Dublin, and S. Senftenberg.
In vitro evaluation of the inhibitory activity of Lactobacillus spp. isolated from crop and ceca of chickens against Salmonella serotypes
Keywords: reprodutora de frango de corte; identificação; Lactobacillus; Salmonella; PCR; broiler breeder; identification; Lactobacillus; Salmonella; PCR